EVALUATING DEBT BURDEN AND REVENUE LEAKAGES ON HUMAN DEVELOMENT IN NIGERIA - JOHN IME JOHN; JOSEPHINE EDEM NSOJA; SULEIMAN GBENGA LAWAL; AKANIYENE BILLY OROK; ANIEKPNO ESSIEN (International Studies Journal)
This study focused on external debt and human capital development in Nigeria. It sought to assess the significance of external debt, and to suggest measures that could enhance its effectiveness and human capital development in Nigeria. To achieve the objective of the research, some external debt and human development capital indicators, using the ex-post facto research design was applied. The data were collated, analyzed and tested using the descriptive statistics and the autoregressive distribution lag (ARDL) data analysis techniques. From the analysis, external debt service payment and external debt burden both non-significantly, but adversely affect human development index in the Nigerian economy. Based on the findings, the study recommended that external debt finance should be channeled to only projects with the highest priority. In doing so, defining the purpose, duration, moratorium requirements and commitments, negotiation fees, etc, including the conditions under which the government can approve and guarantee external loans. Also, one superior method of negotiation should be maintained by the government for varying amortization and fixed interest payment. Also, multi-year rescheduling should be adopted, rather than the year-by-year approach.